Anticancer Effects of Deoxypodophyllotoxin and Juniperus communis L. on Prostate Cancer Cell Lines - Morteza Mahdavi; Mohammad Azadbakht; Akbar Vahdati; Mohammad Shokrzadeh; Ayub Farhadi (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: In this study, the effects of a mixture of deoxypodophyllotoxin/DPT and Juniperus communis L. on apoptosis and cellular inhibition were evaluated. Also, their cytotoxicity effects on prostate cancer cells (PC3 and DU145) and normal cells (HGFs), their anti-inflammatory effects, oxidation properties, and their effects on the expression of androgen receptors (AR) and clusterin (CLU) receptors were evaluated. Materials and methods: In this experimental study, the cells were cultured in DMEM f12 medium containing L-glutamine, penicillin, streptomycin, and 10% FBS. Morphological changes induced by reverse microscope were investigated 24, 48, 72, and 96 hrs after adding pure DPT and juniper extract at 10, 100, 500, 1000 μg/ml. Survival rate was assessed by MTT assay in all three cell lines. The rate of apoptosis in all cell lines was assessed by flow cytometric analysis. The expression levels of AR and CLU genes were evaluated by Real-Time PCR. Results: The 10, 100, 500, 1000 μg/ml of DPT and 500 and 1000 oncentrations of extract after 24 hours caused morphological changes in PC3 and DU145 cells and these changes intensified after 48, 72, and 96 hr. The MTT test showed significant decrease in PC3 and DU145 cell survival levels at 100, 500, and 1000 μg/ml (P<0.001). Also, the extract at 100 and 500 μg/ml significantly reduced the survival of PC3 and DU145 cancer cells (P<0.042). Conclusion: Pure DPT and plant extracts have cytotoxic effects on PC3 and DU145 cells with minimal damage to normal cells.